Supplement to the Revised Statutes of the State of Wisconsin, 1878, Containing the General Laws from 1879 to 1883, with the Revisers' Notes to the Statutes of 1878 and Notes to Cases Construing and Applying These and Similar Statutes by the Supreme Court of Wisconsin and the Courts of Other States, at 848, ch. 181, §4397b(3) (1883) - (:unkn) unknown (My University, 1883)
It shall be unlawful for any person in a state of intoxication to go armed with any pistol or revolver. Any person violating the provisions of this act shall be punished by imprisonment in the county jail not exceeding six months, or by fine not exceeding one hundred dollars.
Keywords: CARRY - DANGEROUS PERSONS